The level of self-esteem among AainBall players varsity of the Hashemite University - Abed Albasit Mobarak AlShorman; Faleh Sultan Abu Eid; Faten Hamdi; Abdulhafed Mabruk Gawar (دراسات وبحوث التربية الرياضية)
This study aimed at identifying the level of self-esteem among AainBall players varsity of the Hashemite University, as well as identifying the differences in the level of self-esteem based on the major variable. The sample of the study consisted of 12 players representing the Hashemite University varsity who won the world university Championship in AainBall 2019, which was held from 24-31/4/2019 in Casablanca. Also, the Indian championship in Kashmir 2022.The researchers used the descriptive approach because it suits the nature of the study and its objectives, a questionnaire was used as a tool to obtain the data of the study, which was prepared by Atrash 2017.The results of the study indicated that the level of self-esteem of AainBall players’ varsity of the Hashemite University was high degree, and there weren’t statistical differences among the study variables.